2020
DOI: 10.11606/issn.2317-0190.v27i1a170815
|View full text |Cite
|
Sign up to set email alerts
|

Redução da força de preensão manual entre idosos longevos

Abstract: Objetivos: Descrever as características sociodemográficas e de saúde dos longevos, identificar a ocorrência da redução da força de preensão manual dos longevos e verificar os fatores associados à redução da força de preensão manual dos longevos. Métodos: Estudo transversal e analítico, com abordagem quantitativa, desenvolvido com 313 idosos longevos da comunidade de uma Macrorregião de Saúde do Estado de Minas Gerais. Na coleta dos dados aplicaram-se: Miniexame do Estado Mental; Questionário estruturado elabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, long-lived individuals are more likely to have reduced handgrip strength (HGS). This reduction, associated with impaired cognitive function, can predict functional limitation 8,9 a higher risk of falls 10 and walking difficulties 11 in older adults. Recent studies demonstrated that the oldest old exhibit marked declines in neuromuscular abilities (strength, power, and endurance) that result in muscle atrophy and sarcopenia.…”
Section: -7mentioning
confidence: 99%
“…Furthermore, long-lived individuals are more likely to have reduced handgrip strength (HGS). This reduction, associated with impaired cognitive function, can predict functional limitation 8,9 a higher risk of falls 10 and walking difficulties 11 in older adults. Recent studies demonstrated that the oldest old exhibit marked declines in neuromuscular abilities (strength, power, and endurance) that result in muscle atrophy and sarcopenia.…”
Section: -7mentioning
confidence: 99%